2014
DOI: 10.3141/2431-12
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Based Condition Assessment of Concrete Bridges

Abstract: Reliable bridge condition assessment is considered the first step, and perhaps one of the most essential elements, of an efficient bridge management system. This consideration stems from the fact that available assessment inputs are constantly interpreted for maintenance decisions and budget allocation to the deserving, intervention-needy bridges within a region's inventory. Thus, carrying out effective bridge assessment is vital to ensure the safety and sustainability of the bridge infrastructure. In practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Rashidi and Gibson (2011) reported that the common defects of concrete bridges may be classified into discoloration, efflorescence, cracking and spalls, corrosion of non-prestressed reinforcement or deterioration of the prestress system and delamination. Moufti (2013) reported that the defects that are common in RC bridge elements include the following:…”
Section: Common Bridge Defectsmentioning
confidence: 99%
“…Rashidi and Gibson (2011) reported that the common defects of concrete bridges may be classified into discoloration, efflorescence, cracking and spalls, corrosion of non-prestressed reinforcement or deterioration of the prestress system and delamination. Moufti (2013) reported that the defects that are common in RC bridge elements include the following:…”
Section: Common Bridge Defectsmentioning
confidence: 99%
“…One of the major advantages of using HER is that it has the capability to deal with incomplete and conflicting evidence without making strong assumption about missing data as required in other soft computing methods. Moufti et al [8] enhanced the application of ER approach by proposing an assessment tool that can handle the prescribed uncertainties in the bridge inspection process and objectively translate the real condition of a bridge through further in-depth measurements. In his model, he hierarchy structured several levels of a concrete bridge under assessment; namely: bridge components, structural elements, and most particularly, the measured defects.…”
Section: Previous and Related Work On Condition Assessmentmentioning
confidence: 99%